Uwarunkowania rozwoju gospodarczego i handlu zagranicznego krajów Europy Środkowo-Wschodniej w okresie międzywojennym (1918-1939): Conditions of economic development and foreign trade of the countries of Central and Eastern Europe in the interwar period (1918-1939) - Klimiuk, Zbigniew (Przegląd Wschodnioeuropejski, 2021)
The economic development of the countries of Central and Eastern Europe in the interwar period did not remove essential structural defects in foreign trade, such as: regionalism, compliance of export and import directions, too much concentration on several markets, low assortment diversity and typically raw material and agricultural export structure. Mutual exchange took place on a small scale and was often unilateral, and its size did not generally exceed 10% of the total turnover of this zone. In addition, it was also characterized by a significant degree of concentration and occurred mainly between neighboring countries and in a narrow range. One of the fundamental reasons explaining the low level of mutual trade was the far-reaching mutual competitiveness of the economies of these countries. The high similarity of export structures and assortments as well as the identity of import needs at a weak level, with a similar export expansion rate, have created significant elements of competition between the economies of the region. In the interwar period, the countries of Central and Eastern Europe were not strongly involved in foreign trade, with the exception of Czechoslovakia. They were generally poorly developed raw material and agricultural countries, exporting mainly raw materials and food to developed countries of Western Europe, and in particular to Germany. Their total share in world trade was at the level of approx. 3% at that time. The low level of involvement of these countries in world trade was indicated in particular by small export volumes per one inhabitant.